Optimization of the extraction of antioxidants and caffeine from maté (Ilex paraguariensis) leaves by response surface methodology - Hartwig, Vanessa Graciela (2013)
Optimal conditions for the industrial extraction of total polyphenols from maté (Ilex paraguarien- sis) were determined using response surface methodology, with two independent variables: ethanol percentage of the extraction solution and liquid to solid ratio. Response variables were total polyphe- nol content, antioxidant capacity, concentration of total polyphenols and caffeine content. The optimal conditions found were a liquid to solid ratio from 8 - 9 w w−1 and ethanol percentage of the extraction solution from 30 - 50 % w w−1. Under these conditions the main predicted values corresponding to leaf extracts were 40 μg chlorogenic acid equivalents mL−1 of original extract, 13 g chlorogenic acid equivalents per 100 g dry matter for total polyphenol content, 22 g Trolox equivalents and 15.5 g ascorbic acid equivalents per 100 g dry matter for antioxidant capacity. The total polyphenol content of twig extracts was 36 % lower than that in the leaf extracts.